2009
DOI: 10.1007/s11269-009-9429-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Framing of Uncertainties in Water Management Practice

Abstract: The importance of problem framing in relation with environmental problems has been stated in various scientific contributions. In this paper we intend to relate it to the issue of uncertainties in water management. Dealing with uncertainties in water management is an important issue and will increase to be so in light of global changes, in particular climate change. To know how uncertainties are framed in water management practice then is important in order to evaluate strategies for dealing with these uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Brugnach and Pahl-Wostl (2007), who argued that the influence of human activities on environmental systems has added substantial complexity to the way water is managed. Later, Isendahl et al (2009) identified important parameters for the framing of uncertainty in water management based on dialogues with water managers in three European basins. Also, Hommes et al (2009) addressed the actors perception and knowledge of water management issues through a participatory decision making process and demonstrated this for the Delta Region in The Netherlands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brugnach and Pahl-Wostl (2007), who argued that the influence of human activities on environmental systems has added substantial complexity to the way water is managed. Later, Isendahl et al (2009) identified important parameters for the framing of uncertainty in water management based on dialogues with water managers in three European basins. Also, Hommes et al (2009) addressed the actors perception and knowledge of water management issues through a participatory decision making process and demonstrated this for the Delta Region in The Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in improved communication between scientists and policy makers on uncertainty in environmental management including water resources management (Isendahl et al 2009;Wardekker et al 2008). Impacts of wrong decisions can be far-reaching and for decision makers it is important to have knowledge on how reliable information is on which management decisions and measures rely.…”
Section: Introductionmentioning
confidence: 99%
“…A frame is the context through which a person interprets the world, also known as his or her perception, perspective, worldview, mental model, script or schema (Schön and Rein 1994 ;Isendahl et al 2009 ;Dewulf et al 2009 ).…”
Section: Framing Choicesmentioning
confidence: 99%
“…Polycentric systems that create multiple centers of authority but still maintain adequate vertical and horizontal coordination improve performance across a range of socioeconomic contexts (Pahl-Wostl et al 2012). These studies also identify important barriers to more adaptive forms of governance, which would make dealing with climate variability and change easier, for example, with respect to cooperation and information sharing (Isendahl et al 2009). These observations suggest value in a more detailed exploration of the relationships between specific water governance regime features in river basins and problem structures including key elements of social and ecological context.…”
Section: Introductionmentioning
confidence: 99%